Gorgeous lies - McPhee, Martha (New York : Harcourt Inc., 2002)
The family of dying therapist Anton Furey finds its precarious balance upset by their efforts to make peace with Anton and each other.
Also issued online.
Keywords: Parent and adult child -- Fiction; Terminally ill parents -- Fiction; Father and child -- Fiction; Communal living -- Fiction; Stepfamilies -- Fiction; Domestic fiction